TOXICITY ASSESSMENT ON NINE SPONGES SPECIES FROM SPERMONDE ARCHIPELAGO - Ajuk Sapar; Alfian Noor; Nunuk Hariani Soekamto; Ahyar Ahmad; Tri Aryono Hadi (Hasanuddin University, 2015)
Toxicity assessment have been conducted on nine sponges species collected from Spermonde Archipelago namely Kapoposang Island, Samalona Island and Lanjukang Island. Toxicity assessment was using Brine Shrimp lethality Test (BST) method againts sponge extracts. Theresults test were expressed as 50% lethal concentration (LC50) to Artemia salina and correlated with prospecting extract potential as anticancer. All extracts obtained from smallscale extraction by methanol. Test results as follows: Acanthostrongylophora ingens (24.830 μg/mL), Hytios erectus (46.140 μg/mL), Stylissa massa (>1000 μg/mL), Theonella sp (35.010 μg/mL), Niphates olemda (87.500 ppm), Haliclona (Reniera) fascigera (78.160 μg/mL), Petrosia (Petrosia) sp (3.008), Callyspongia (Euplacella) biru (0.515 μg/mL). The test results showed that seven species are potential as anticancer with LC50 value ≤ 500 ppm and only Stylissa massa extracts was not potential as anticancer.